An insight into novel therapeutic potentials of taxifolin - Liu, Yang; Shi, Xiaolu; Tian, Ye; Zhai, Shaobo; Liu, Yuyan; Xiong, Zhengrong; Chu, Shunli (Frontiers in Pharmacology, 2023)
Taxifolin is a flavonoid compound, originally isolated from the bark of Douglas fir trees, which is often found in foods such as onions and olive oil, and is also used in commercial preparations, and has attracted the interest of nutritionists and medicinal chemists due to its broad range of health-promoting effects. It is a powerful antioxidant with excellent antioxidant, anti-inflammatory, anti-microbial and other pharmacological activities. This review focuses on the breakthroughs in taxifolin for the treatment of diseases from 2019-2022 according to various systems of the human body, such as the nervous system, immune system, and digestive system, and on the basis of this review, we summarize the problems of current research and try to suggest solutions and future research directions.